Manajemen Operasional Checking-In Terhadap Kapal Keagenan PT. Serasi Shipping Indonesia Cabang Banjarmasin - Noor Fathuliansyah; Muhammad Ilham; Wahyu Akbar Arisiansyah; M.Irfan Noor (Majalah Ekonomi, 2026)
This study aims to gain an in-depth understanding and generate practical recommendations for improving effective and sustainable ship check-in management at PT. Serasi Shipping Indonesia, Banjarmasin Branch. The study used a qualitative descriptive approach, focusing on analyzing the ship check-in management process based on the POAC (Planning, Organizing, Actuating, Controlling) management function. The results indicate that the ship check-in process has been implemented systematically through planning stages, including document preparation and initial coordination with relevant agencies, resource organization and activity scheduling, ship inspections by a cross-agency team, and ongoing process monitoring and evaluation. The implementation of digital systems such as Inaportnet, online communication, and the implementation of one gate clearance also support service efficiency. Overall, the ship check-in management at PT. Serasi Shipping Indonesia, Banjarmasin Branch, can serve as an example of good agency operational governance practices, supported by effective communication, direct supervision, and flexibility in operational scheduling.